Overview of Method for Detecting of Streptococcus mutans and Lactobacillus in Saliva - Sounah, Sabah A.; Madfa, Ahmed A. (Austin Publishing Group, 2020)
Saliva provides some real potential in evaluating dental caries risk. Lack of saliva predisposes the development of atypical or unusual dental decay, i.e., cervical, incisal or in cusps tips, as well as radicular lesions. This is due to that saliva contains various microbes and host biological components that could be used for caries risk assessment. This review focuses on the research topics that connect on some methods used for detecting of Streptococcus mutans and Lactobacillus in Saliva.